What is the best strategy to measure Software Quality? - Martínez, Daniel Ignacio (2024)
The success of a software product basically depends on catering for the users´ need. This implies, providing the product on time and within the estimated costs so as to fulfill the specified requirements and the users´ expectations. In this respect, it is necessary to have a strategy that allows to monitor the software product quality, and from this point onwards make the necessary adjustments with the sole objective of enhancing the final product. Taking this into consideration, this article proposes to involve the user during the whole life cycle process “Testing”, taking as a basis the ISO 9126 standard, with the ultimate aim of evaluating and upgrading the software quality, leading to the end users´ contentment.